What affects the main engine of growth in the European economy? Industrial interconnectedness and differences in performance of business services across the EU25 - Maciej Sobolewski; Grzegorz Poniatowski (Center for Social and Economic Research (CASE), 2013)
The main purpose of this study is to determine what are the main factors which stand behind the diversity in performance of business services measured by their contribution to growth in the EU Member States. We show that in addition to typical growth factors which enhance labour productivity, also the extent of interconnectedness of business services with upstream industries is important to explain service-based economic growth. The analysis yields two interesting results. Firstly, the authors show that patterns of industrial interconnectedness of business services are considerably diversified across the EU Member States indicating large differences in the integration of services as supplier with other sectors on a country level. Secondly they show that the diversified growth performance of business services across the EU25 countries can be explained by differences in labour productivity and differences in forward linkages. The results indicate the fundamental role of business services as the main engine of growth in the European economy. This service-based growth is channelled mainly through increases in labour productivity and forward interconnectedness of services with downstream industries. On the policy making level the results indicate that investment in human and intangible capital are crucial for the service-dominated economy as they not only enhance economic growth inside knowledge intensive services but also facilitate transmission of growth impulses to downstream industries by increasing diffusion and integration of services as suppliers of high value added inputs to the economy.
Keywords: D57; L52; R15; 330; Industrial Linkages; Business Services; Growth; Multipliers; Input-Output; Interindustrielle Verflechtung; Dienstleistungssektor; Unternehmensdienstleistung; Wertschöpfung; Wirtschaftswachstum; EU-Staaten